Legal recognition, Social Exclusion: Rethinking the Third Gender Framework in Post-NALSA India - Kiran Bedi1 Dr. Supriti2 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This conceptual paper critically examined the incoherence between legal recognition and social inclusion of Third Gender individuals in post-NALSA India, using Haryana as a case study. The study interrogated the paradox of recognition how state sanctioned identities failed to translate into meaningful access to welfare, employment, education, and healthcare. It highlighted the symbolic power of Third gender category and explored traditional cultural spaces, such as deras and guru-chela hierarchies there. Deras offer nominal acceptance and reinforce internal exclusion and reliance on precarious livelihoods. By situating the Third gender within broader structures of state the paper called for recalibrated framework of inclusion that move beyond identity recognition and toward institutional integration. The study drew selective international comparisons to provide context for India’s trajectory. In conclusion, the paper offered a reconsidered conceptual pathway for policy and academic discourse. It urged future scholarship to foreground social justice, material equity, and cultural transformation alongside legal recognition.